Sistem Pendukung Keputusan Pemilihan Personel Yon Zipur I Dhira Dharma Ke Daerah Rawan Konflik Menerapkan Metode MOORA - Rizki Amalia Siregar (STMIK Budi Darma, 2019)
Decision making in an organization is the result of a continuous process of communication and participation of the entire organization. The results of these decisions can be agreed statements between alternatives or between procedures or achieving certain objectives. The Multi Objective Optimization method on the Base of Ratio Analysis (MOORA) using this method can provide the best alternative in selecting Yon Zipur I / DD personnel. This method has a good level of selectivity because it can determine the objectives of conflicting criteria. Where criteria can be of beneficial value or benefit.